Die subjektiven und die objektiven Dimensionen des sozialen Lebens. Simmels sozio-anthropologische Perspektive - Martinelli, Monica (Simmel Studies)

(untitled) (Edizioni ETS, 2023)
Simmel’s concern is to analyse the relationship between subjective and objective dimensions and at the same time to search for a horizon of meaning that sustains this relationship. A topic that Simmel analysed from many viewpoints. The focus of this paper is mainly on the socio-anthropological point of view. According to Simmel, when the subjective and objective dimensions are seen as contradictory, the integrity of the individual is undermined. The subject's experience in modernity is submitted to a logic characterised by a strong dualism. Nevertheless, the relationship between the subjective and the objective dimension shapes our experience: society could be seen as the progressive development of this nexus. Simmel suggests that one and the other poles are complementary in a relationship of reciprocity and mutual limitation - an expression of the original duality of life which embodies “the whole being”.